2022
DOI: 10.3390/w14121951
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Perfluorinated and Pharmaceutical Compounds in Plastics: A Molecular Simulation Study

Abstract: The aim of the current study is to investigate the effect of temperature and degree of polymerisation on the thermodynamic interaction of perfluorinated compounds (PFCs) into plastics. The occurrence of contaminants of emerging concern such as pharmaceutical drugs, PFCs, microplastics (MPs), etc., in sources of drinking water have posed significant health risks to aquatic life and humans in recent years. These organic pollutants can interact with MPs and pose much higher health risks; consequently, MPs become … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Although we are unable to verify it in this work, Khumalo et al hypothesized that plastic pore-filling could be an important mechanism of PFAS partitioning, especially at high temperatures due to polymer (pore) expansion. 56 Based on the Gibb's free energy (ΔG) we obtained (Figure 3 h), which ranged from -16.4 kJ/mol (for PFBA) to -22.5 kJ/mol (for PFOS), we concluded that the adsorption of the five PFAS to the secondary PET MPs is thermodynamically spontaneous at 25°C and would occur in surface waters. The ΔG of the adsorption of PFAS to the secondary PET MPs became more negative as temperature increased (Table S8), which is reasonable given that it is an endothermic process (ΔH = 14.0 to 41.0 kJ/mol).…”
Section: Role Of Temperaturementioning
confidence: 75%
“…Although we are unable to verify it in this work, Khumalo et al hypothesized that plastic pore-filling could be an important mechanism of PFAS partitioning, especially at high temperatures due to polymer (pore) expansion. 56 Based on the Gibb's free energy (ΔG) we obtained (Figure 3 h), which ranged from -16.4 kJ/mol (for PFBA) to -22.5 kJ/mol (for PFOS), we concluded that the adsorption of the five PFAS to the secondary PET MPs is thermodynamically spontaneous at 25°C and would occur in surface waters. The ΔG of the adsorption of PFAS to the secondary PET MPs became more negative as temperature increased (Table S8), which is reasonable given that it is an endothermic process (ΔH = 14.0 to 41.0 kJ/mol).…”
Section: Role Of Temperaturementioning
confidence: 75%
“…The modified Flory-Huggins approach was employed as implemented in the Blends module of Materials Studio and as applied in the previous studies. 31,34,35 Briefly, the mixing energy (E mix ), coordination number, and free energy were determined as estimated by sampling from energetically favorable configurations using the volume constraint method, yielding average properties over an ensemble of molecular configurations. 31 After the temperature-dependent interactions were determined, the binodal and spinodal curves were computed within the framework of the off-lattice Flory-Huggins theory, along with the critical point of the mixture, thereby yielding the binary phase diagram.…”
Section: Molecular Simulationmentioning
confidence: 99%